PENGARUH METODE PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP PEMAHAMAN KONSEP MATERI RUANG VEKTOR MAHASISWA JURUSAN TEKNIK INFORMATIKA UNIVERSITAS PUTRA INDONESIA ‘YPTK’ PADANG - Deby Erdriani (Universitas Batanghari Jambi, 2017)
The aim of this research is to provide any chances for students to involve actively in thinking process and learning activities. In this case, the learning process is mainly centered on students that is to learn the teaching materials and do the discussion to solve the problem on studies, thus, finally they can improve students grade. The learning cooperative Model, Numbered Heads Together, is a type of cooperative learning which emphasized on the special structure that is designed to influence the student interaction pattern and aiming to increase the academic control. Based on the result of this research conclude that through the Mann-Whitney on α = 0,05 test, as a whole, high and low group, found that as entirety is not differed much significant between the experimental class that is used the Numbered Heads Together method and control class that is used the conventional method. In lower group, there is seen the significant difference between experimental classes that is used Numbered Heads Together method and control class that is used the conventional method.Keywords: Cooperative Learning, Numbered Head Together, Conventional Method, MANN-WHITNEY, SPSS